(untitled) (Praxis Educativa, 2012)
This paper pretends to show the difference between literal and non literal language, and emphasizes the fact that both of them are used in the everyday language. The literal language does not present any difficulty for the listener to understand it because it only uses a decoding process to reach the semantic level of the language. The metaphorical language, in opposition, not only needs to be decoded but requires the listener to develop inferential processes that let him understand what the speaker means by that statement in that specific moment of the communication; that is to say, the listener needs a pragmatic knowledge given to him by the context, the speaker and his intentions to understand the utterer’s meaning. This paper shows how the cognition and the thought formation processes are achieved specially through the use of the metaphorical language.